CYBER PR DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI DISKOMINFO KABUPATEN BOGOR (STUDI KASUS PADA WEBSITE LARAS ONLINE) - Dina Affalia Utomo (2022)
The government has a responsibility to provide quality services to the community. Many efforts have been made by both district and city governments that have focused on improving the quality of public services, one of which is Diskominfo Bogor through LARAS Online. This study aims to discuss how cyber PR Diskominfo Bogor Regency in improving the quality of public services and obstacles in improving the quality of public services on the LARAS Online website using system theory and boundary spanning functions. The method used is a case study with a qualitative approach. Data collection techniques were carried out by in-depth interviews, observation and documentation. The researcher used data analysis techniques by Robert K. Yin, namely matchmaking patterns, making explanations and time series analysis. This study uses triangulation of source validity data. The results showed that the Bogor District Communications and Information Office had undergone cyber PR activities in improving the quality of public services, including conducting socialization through social media, developing websites and conducting technical guidance to all related SKPD. Some of the activities that have been carried out are considered still lacking in improving the quality of public services. Constraints experienced by Diskominfo Bogor in improving the quality of public services are the lack of coordination between officers and SKPD and an unstable network that hinders the complaint service process.